Interactive Debate Strategies for Enhancing Arabic Speaking - Solehudin, Muhamad (Department of Arabic Education of State Collage for Islamic Studies of Mandailing Natal, 2024)
Despite years of traditional Arabic language instruction, many students still struggle to express themselves confidently and fluently in real-world conversations. This alarming gap underscores the urgent need for innovative pedagogical strategies that go beyond rote memorization and passive learning. This study investigates the effectiveness of interactive debate strategies in enhancing Arabic speaking proficiency, offering a dynamic platform for real-time communication, critical thinking, and confidence-building. Utilizing a qualitative descriptive approach, data were collected through classroom observations, interviews with educators and students, and reflective journals. The study involved 60 participants, selected through purposive sampling to represent varying proficiency levels. The findings reveal that interactive debates significantly improve fluency, vocabulary acquisition, and critical argumentation skills, while also fostering psycholinguistic benefits such as reduced speaking anxiety and better cognitive control. However, challenges like time constraints, preparation gaps, and language disparities were observed. To address these barriers, practical solutions including pre-debate workshops, flexible scheduling, and scaffolded participation are proposed. This study bridges a crucial gap in Arabic language pedagogy by presenting a structured framework for implementing interactive debates, ultimately promoting sustainable language learning outcomes and empowering students to speak Arabic with clarity, confidence, and cultural awareness.